Character Education Strategy in Pesantren: Integrating Morals and Spirituality - Sheva Bayu Firmansyah; Zaenal Abidin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research was conducted because of the importance of an in-depth understanding of the character education strategies implemented by teachers at the Pesantren Mahasiswa (PPM) Al-Musawwa. This research method uses a qualitative descriptive method. The data collection techniques used are observation and interview techniques. This data analysis refers to the steps from Miles Huberman: data collection, data reduction, data presentation, and conclusion. The research findings reveal that character education at PPM Al-Musawwa is a holistic process that encompasses students' moral, spiritual, and ethical development. This process is integrated through activities both inside and outside the classroom, with teachers serving as role models. However, significant challenges arise from the negative influence of technology and social media, as well as the diverse social backgrounds of the students, which require careful attention in the character formation process. Despite these challenges, the strategies employed aim to cultivate a generation of students who are not only academically proficient but also possess noble morals, integrity, and a strong sense of responsibility in alignment with Islamic teachings.